The PEMBERDAYAAN MASYARAKAT DALAM PENERAPAN APLIKASI WEB TENTANG PREDIKSI DAN PENCEGAHAN RESIKO PADA IBU HAMIL : COMMUNITY EMPOWERMENT IN THE IMPLEMENTATION OF WEB APPLICATIONS ON RISK PREDICTION AND PREVENTION IN PREGNANT WOMEN - Hipni, Rubiati; ZAKIAH; Vonny Khresna Dewi (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Early detection and prevention of risks in pregnant women are very important to ensure the health of both mother and fetus. Lack of access to information leads to limited knowledge. Therefore, efforts are needed to improve risk prediction in pregnant women and risk prevention efforts in pregnant women. The community of Cempaka Village, especially pregnant women who are vulnerable to risky pregnancies, and Posyandu cadres are the main partners in handling this problem. Lack of access to information leads to limited knowledge. Therefore, efforts are needed to improve risk prediction in pregnant women and risk prevention efforts in pregnant women. The solution used to solve the problem in Cempaka Village is to provide counseling, training, education and assistance related to Prediction and Prevention of Risks in Pregnant Women by implementing a Web Application. This community service aims to increase public awareness of the importance of early detection and Screening Efforts for Pregnant Women at Risk, Increase accessibility of health information for pregnant women in the Cempaka Village area. Increased knowledge about Prediction and Prevention of Risks in Pregnant Women and reduce risks in pregnant women. The implementation method includes an initial survey to assess the level of public awareness and knowledge regarding the health of pregnant women with a questionnaire, training by providing education to 12 pregnant women and 12 Posyandu cadres, practice and assistance in using information-based web applications that include Prediction and Prevention of Risks in Pregnant Women, Implementation of Web Applications to the community, monitoring their use and Evaluation. The results of the activity increased the knowledge and skills of pregnant women and cadres in using applications for early detection of risks in pregnant women. It is recommended that this activity can be carried out continuously in collaboration with other health workers and the sub-district.